2019
DOI: 10.1093/rheumatology/kez255
|View full text |Cite
|
Sign up to set email alerts
|

CXCL13 as biomarker for histological involvement in Sjögren’s syndrome

Abstract: Objectives SS is an autoimmune condition characterized by systemic B-cell activation, autoantibody production and ectopic germinal centres’ formation within the salivary gland (SG). The extent of SG infiltrate has been proposed as a biomarker of disease severity. Plasma levels of CXCL13 correlate with germinal centres’ activity in animal models and disease severity in SS, suggesting its potential use as a surrogate serum marker to monitor local B-cell activation. The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…29 Published data on CXCL13 suggest that it may be a biomarker that reflects GC activity and correlates with the extent of salivary gland pathology. 7 Therefore, the iscalimab-dependent reductions in CXCL13 that preceded clinical improvement observed here, might reflect suppression of the structure and function of GCs, and possibly salivary gland ELS. Given that the individuals in this study also had extraglandular involvement based on their ESSDAI≥6 scores, the clinical benefit observed with iscalimab may also extend to extraglandular tissues.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…29 Published data on CXCL13 suggest that it may be a biomarker that reflects GC activity and correlates with the extent of salivary gland pathology. 7 Therefore, the iscalimab-dependent reductions in CXCL13 that preceded clinical improvement observed here, might reflect suppression of the structure and function of GCs, and possibly salivary gland ELS. Given that the individuals in this study also had extraglandular involvement based on their ESSDAI≥6 scores, the clinical benefit observed with iscalimab may also extend to extraglandular tissues.…”
Section: Discussionmentioning
confidence: 63%
“…4 Recent data have indicated that the presence of salivary gland ELS 5 and increased systemic levels of CXCL13 6 correlates with disease severity, implicating ELS and accompanying B cell hyper-reactivity in pSS pathology. 7 B cell activation, immunoglobulin class-switching, and GC formation are regulated by various immunological costimulatory pathways, notably CD40-CD154 interactions. 8,9 Reports on the expression of CD154 and CD40 on salivary gland-infiltrating T and B cells respectively, 10,11 suggest that T cell-B cell interactions via this pathway may contribute to sialadenitis and ELS formation and function.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that specific B-cell markers such as monoclonal immunoglobulins, free light chains found in the serum and urine, and increased serum BAFF levels are associated with lymphoma in pSS patients [9,20]. Based on these studies, we might expect a correlation between CXCL13 levels and B-cell markers.…”
Section: Discussionmentioning
confidence: 89%
“…CXCL13 is found in human blood, plasma and serum and high CXCL13 levels have been associated with pSS and systemic lupus erythematosus (SLE) [18][19][20][21]. A previous study that included patients from the Assessment of Systemic Signs and Evolution of Sjögren's Syndrome (ASSESS) cohort showed that serum CXCL13 and CCL11 levels were elevated in pSS patients with high EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) score, B-cell activation and NHL [19].…”
Section: Introductionmentioning
confidence: 99%
“…Within those aggregates, the development of ectopic germinal centers (GC), characterized by full segregation in T and B cell zones, formation of CD21+ follicular dendritic cell networks has also been described, in association with local B cell proliferation and affinity maturation [15]. This phenomenon is associated with disease severity, autoantibody production, and lymphoma development [16].…”
Section: Introductionmentioning
confidence: 99%